Managing Growth: The Role of Export, Inflation and Investment in three ASEAN Neighboring Countries - Audrey, Liwan; Lau, Evan (Munich University Library, 2007)
This study investigates the relationship between export, inflation, investment and economic growth for three ASEAN countries namely Indonesia, Malaysia, and Thailand. In general, the results revealed that export has a positive impact on growth. As for, Malaysia and Thailand, inflation has a negative impact on growth; while for Indonesia it has a positive impact. The inflation rate for Indonesia is almost consistent for a several years, which have lead to a positive relationship between inflation and growth. However, there is also a modest increase in the rate of inflation for certain years. The results also shows that investment have a positive impact on growth for Indonesia, Malaysia and Thailand.